Pengaruh Interaksi Bahan Mineral dan Bahan Organik Terhadap Sifat Kimia Ultisol dan Produksi Tanaman Sawi - Elva Rizkya Masni; Bintang Sitorus; Purba Marpaung (Universitas Sumatera Utara, 2015)
This study aimed to test the chemical properties of Ultisol and Brassica production by a combination of organic matter and minerals. This research was conducted at the gauze house, Compost Centre, and Research Technology Laboratory, Agriculture Faculty, University of North Sumatra, Medan. The research was conducted from September 2014 until May 2015. The research design used a randomized block design (RAK) by 2 factors treatments and two replications. The first factor is a mineral, M1: ash 250 g / 5 kg soil and M2: portland cement 62.5 g / 5 Kg of soil. The second factor (organic matters) are compost of durian skin by kefir activator (O1), compost of durian skin by yogurt activator (O2), compost of bagasse by kefir activator (O3), compost of bagasse by yogurt activator (O4), compost of sweet potato canopy by kefir activator (O5), compost of sweet potato canopy by yogurt activator (O6), compost of market waste by kefir activator (O7) and compost of market waste by yogurt activators (O8) each of all was 250 g / 5 kg soil. The results showed that organic matter gived significantly effect to increased plant fresh weight. But the effect was not significant to roots fresh weight, soil reaction (pH H2O) and C-organic. Mineral treatments gived significantly to increased the soil reaction (pH H2O). But the effect was not significant to plant fresh weight, root fresh weight and C-organic. Interactions of both treatments gived significantly to increased the soil reaction parameters (pH H2O) of all parameters observed.Key words :Ultisol, organic matters, minerals, brassica